Interplay of cellular states: Role of delay as control mechanism - Singh, Shakti Nath; Chanu, Athokpam Langlen; Malik, Md. Zubbair; Singh, R.K. Brojen (Physica A, 2021)
Delay is ubiquitous, no matter how small or big it is. Experimental evidences show the existence and importance of time delayed reactions specially in biological systems. We studied the interplay of delay and noise in some biological models, analytically and computationally. The analytically solved P(x,t) of gene regulation process shows universal class of Poisson process at large initial population and large x. Fano factor which measures noise in the system is found to be delay dependent. Analytical results give the possibility of noise-induced control of the system dynamics driven by delay. From analytical results, time delay creates possible conditions to the system to trigger various mechanisms such as correlated activity, coherence, etc. This indicates the interplay of delay and noise in regulating and controlling the system. To see this, we simulated some biological systems (gene regulation, circadian rhythm, repressilator, brusselator) using delay stochastic simulation algorithm. Simulation results show various mechanisms such as delay-induced onset of oscillating states (which could be active states where the system can establish coherence among the system variables), delay-induced switching-off of the oscillating states (which may correspond to inactive state or system failure), delay-induced coherent bistable states (where the system can stay longer to make decisions about the fate of the system). From simulation studies, we thus observed that delay and noise could play significant roles in regulating and controlling system dynamics, as also pointed out by analytical results. •The role of delay in various stochastic biological systems are presented.•Analytical solution of both delay and non-delay stochastic systems are presented.•We showed a variety of models in which delay plays different and important roles.•The significant roles of noise measured by Fano factor are also discussed.